MEMBANGUN KESADARAN LINGKUNGAN LEWAT EDUKASI SAMPAH DI SDN 15 SUMANIK - Ramaita; Nabilla; Amalia Rahmatika,; Aulia Rahman; Lativa Angri,; Ocha Meidita Putri (STKIP Subang, 2025)
Poor waste management remains a major environmental problem, including in elementary schools. Students' lack of understanding of how to separate organic and inorganic waste can negatively impact their health and the cleanliness of the surrounding environment. Therefore, the goal of this community service activity was to raise awareness and understanding of the importance of waste management among students at SDN 15 Sumanik by providing them with direct instruction and practice in sorting waste. Teachers and students in grades IV, V, and VI of SDN 15 Sumanik were partners in this activity. Outreach, field practice, interactive materials, and waste sorting demonstrations were among the methods employed. The results of the activity showed that students had a better understanding of waste types and were more adept at sorting waste independently. Furthermore, educators stated that this activity made a positive contribution to enhancing environmentally conscious character education in schools. This education not only increased environmental awareness but also instilled a sense of responsibility in students for maintaining the cleanliness of their school environment. These results are essential because contextual education in elementary schools will develop a young generation that cares about the environment.